Proteomics of the red alga, Gracilaria changii (Gracilariales, Rhodophyta) - Wong, P.F.; Tan, L.J.; Nawi, H.; AbuBakar, Sazaly (2006)
The application of proteomics in alga research is still quite limited. The present report describes the establishment of the proteome of a red alga of economic importance, Gracilaria changii (Xia et Abbott) Abbott, Zhang et Xia. Initially, four protein extraction methods including direct precipitation by trichloroacetic acid/acetone, direct lysis using urea buffer, Tris buffer, and phenol/chloroform extraction were compared for their suitability to generate G. changii proteins for two-dimensional gel electrophoresis (2-DE). The phenol/chloroform protein extraction method gave the best 2-DE resolution of the proteins. Using these 2-DE gels and mass spectrometry, several proteins including pigment proteins, metabolic enzymes, and ion transporters were identified. These findings highlight the potential of using proteomic approaches for the investigation of G. changii protein function.